2015
DOI: 10.5123/s2176-62232015000300007
|View full text |Cite
|
Sign up to set email alerts
|

Turismo de risco para esquistossomose mansônica em Porto de Galinhas, Estado de Pernambuco, Brasil

Abstract: RESUMOApesar do balneário Porto de Galinhas -situado no Município de Ipojuca, Estado de Pernambuco, Brasil -ser o destino turístico mais procurado no Estado, inúmeras pousadas vêm sendo construídas em áreas sem saneamento, onde proliferam criadouros e focos de Biomphalaria glabrata, o principal caramujo transmissor da esquistossomose mansoni. A localidade é considerada endêmica para esta doença e, na estação das chuvas, o risco de exposição aumenta, com ruas e quintais repletos de caramujos, o que promove a in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…The relationship between elevation (DEM) and rainy season was observed in this study, showing that the lower slope area suffer the influence of precipitation, causing the accumulation of water, which is an aggravating factor for the disease epidemiology and transmission. Barbosa et al 11 , using a distance map and a water expansion map, found an association between patients with schistosomiasis and the proximity to breeding sites or foci of Biomphalaria in Porto de Galinhas, municipality of Ipojuca, Pernambuco. In Itamaracá, the analysis performed through the distance maps showed that the main centers of active transmission of the disease are located in the streets around schools and local helthcare center, places of compulsory and systematic access by the population.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between elevation (DEM) and rainy season was observed in this study, showing that the lower slope area suffer the influence of precipitation, causing the accumulation of water, which is an aggravating factor for the disease epidemiology and transmission. Barbosa et al 11 , using a distance map and a water expansion map, found an association between patients with schistosomiasis and the proximity to breeding sites or foci of Biomphalaria in Porto de Galinhas, municipality of Ipojuca, Pernambuco. In Itamaracá, the analysis performed through the distance maps showed that the main centers of active transmission of the disease are located in the streets around schools and local helthcare center, places of compulsory and systematic access by the population.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]7,12 In 2000, an outbreak of acute schistosomiasis occurred in Porto de Galinhas. 14 Interventions took place and the disease was believed to have been controlled at that coastal resort. However, a new survey was conducted in 2011 and new cases with characteristics of the chronic form of the disease were found.…”
Section: Methodsmentioning
confidence: 99%
“…However, a new survey was conducted in 2011 and new cases with characteristics of the chronic form of the disease were found. 14,15 In addition, areas vulnerable to the establishment of the transmission cycle, with presence of bodies of water and snails, have been reported in the Sertão macro-region since 2011. 13 This study was based on data from PCE Form 101, a standard SISPCE form intended to gather information about field activities carried out by health departments in endemic municipalities.…”
Section: Methodsmentioning
confidence: 99%
“…13 n. 3, e2151 -Taubaté 2018 peripheral foci overflow and infected snails are carried into the streets. These artificial and peridomestic foci are formed by wastewater that is discharged into the environment, in communities that dwell in areas surrounding the resorts (Barbosa et al, 2015a;2015b).…”
Section: Resultsmentioning
confidence: 99%